A sub-2-dB noise figure linear wideband low noise amplifier in 0.18 µm CMOS. (September 2017) - Jafarnejad, Roya; Jannesari, Abumoslem; Sobhi, Jafar
Abstract: This paper presents a sub-2-dB Noise Figure (NF) wideband differential Common Gate (CG) Low Noise Amplifier (LNA) in 0.18 µm CMOS technology. The circuit benefits from several new techniques to improve the overall performance. A new current bleeding scheme is proposed in which not only enhances the gain of the circuit but also improves transconductance and noise performance simultaneously. In addition, double positive feedback is employed with only an auxiliary NMOS transistor to break the trade-off between noise and input matching condition of the CG structure. Moreover, the added transistor is biased in moderate inversion region to form pre-distortion performance and sink third order nonlinearity of main transistors at the input. Thus, low noise figure is obtained simultaneous with good linearity. Post-layout simulation results in TSMC 0.18 µm RF-CMOS show a voltage gain of 20.1 dB with a −3 dB bandwidth of 0.38–2.7 GHz, while S11 is below −10 dB over the frequency band. The minimum NF equals to 1.88 dB and an average NF of 2.04 dB is achieved over the frequency band. Third Input Intercept Point (IIP3) of the proposed circuit is +6 dBm. The circuit occupies an area of 0.055 mm 2 while consuming 2.55 mA from a 1.2-V supply voltage. Highlights: A sub-2-dB wideband differential common gate low noise amplifier is presented in 0.18 µm CMOS technology. A new current bleeding scheme is proposed which improves gain, effective transconductance and noise performance. Double positive feedback is proposed using only an NMOS transistor to reduce noise figure. NF reduction and gain enhancement is simultaneous with linearity improvement employing pre-distortion technique. The circuit is inductoreless and suitable for wideband low power applications.